1998
DOI: 10.1007/s001340050590
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tolerance in patients with acute respiratory failure

Abstract: Thus, our data provide circumstantial evidence that the lungs of patients with acute respiratory failure might exhibit some relative resistance to prolonged oxygen exposure. Therefore, it might be worthwhile carrying out a prospective study of different FIO2 strategies in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This damage may be produced by the underlying disease process, the inflammation associated with ARDS or the use of excessive tidal volumes during ventilation 56 while any effects of hyperoxia remain unknown 7…”
Section: Pathophysiologymentioning
confidence: 99%
“…This damage may be produced by the underlying disease process, the inflammation associated with ARDS or the use of excessive tidal volumes during ventilation 56 while any effects of hyperoxia remain unknown 7…”
Section: Pathophysiologymentioning
confidence: 99%
“…This median FiO 2 level was equal to 0.70 [IQR 0.6-0.8] in our study. The adjustment of FiO 2 is still a matter of controversy [7,8]. The lung of patients with ARDS might exhibit some relative resistance to prolonged oxygen exposure [7].…”
Section: Dear Editormentioning
confidence: 99%
“…Supraphysiological concentrations of oxygen in inspired gas (hyperoxia) are frequently required to treat hypoxaemia in patients with ALI [116]. Prolonged exposure to high oxygen levels causes damage in many normal organs and tissues [117].…”
Section: Inspired Oxygen Concentrationmentioning
confidence: 99%
“…It has been shown that if patients with ALI breathe 100% oxygen, an increase in intrapulmonary shunting occurs as a result of the collapse of unstable alveolar units with very low V̇/Q̇ ratios [125]. In a retrospective study over 10 years of 74 patients with acute respiratory failure ventilated continuously with an F I O 2 > 0.9 for at least 48 h, no difference in duration of exposure to this F I O 2 was found between survivors and non‐survivors (5.6 days vs. 5.9 days) [116]. However, on multivariate analysis, exposure to an F I O 2 of > 0.9 was significantly associated with death, presumably as a result of more severe ALI in this group.…”
Section: Inspired Oxygen Concentrationmentioning
confidence: 99%